Proszynellus—a new jumping spider genus from Australia (Araneae: Salticidae) - Patoleta, Barbara; Żabka, Marek (Zootaxa, 2015)
The new genus Proszynellus is described from Western Australia to include three new species: P. nasalis (♂♀), P. wandae (♂♀) and P. occidentalis (♂), the first being designated the generic type. Diagnosis, descriptions, illustrations and distributional maps for all species are provided. Based on morphological characters, especially male palp and vulva, the genus is tentatively placed in Heliophaninae, being possibly close to Menemerus Simon.